STOFFBERG, Theunis Christoffel Inventory of documents - STOFFBERG, Theunis Christoffel (ARCA, 2018)
Private papers of T.C. Stoffberg, Transvaal Senator [1928-1937].
COVERAGE 1878-1937; 27 Files; 0,55 Metres.
Keywords: STOFFBERG, Theunis Christoffel; Inventories; Politicians; National Party